AQUEOUS WOOD-ASH EXTRACT OF PARKIA BIGLOBOSA IMPAIRED SPERMATOGENESIS IN MALE ALBINO MICE - Auta, Timothy; Hassan, A. T. (FUDMA JOURNAL OF SCIENCES, 2023)
Wood-ash extracts are used as food additives and medicinals by different ethnic groups in Nigeria. Despite these uses, there is paucity of information on the possible adverse effects on the reproductive health in mammals. This study assessed the toxicity of aqueous wood-ash extract of Parkia biglobosa on reproductive organ in male albino mice. Four different dose levels of wood-ash extract of Parkia biglobosa [0 (control), 5, 50 and 100 mg/kg body weight] were orally administered to 20 mice (5 per group) for seven (7) consecutive days. After 35 days from first day of extract administration, blood samples were collected by retro-orbital phlebotomy and assayed for serum follicle stimulating hormone (FSH), Luteinizing hormone (LH) and testosterone. Mice were sacrificed subsequently by cervical dislocation and testes harvested to examine gonadosomatic index, sperm motility, sperm count, sperm morphology and testicular histopathology using standard methods. ANOVA was used to determine the significant difference among treatments, at P
Keywords: Wood-ash extract, Reproductive Toxicity, Sperm Quality and Quantity, Seminiferous tubules, Reproductive Hormones